B-cell dynamics underlying poor response upon split-inactivated influenza virus vaccination - Reis, Laise Rodrigues; Silva-Moraes, Vanessa; Teixeira-Carvalho, Andréa; Ross, Ted M. (Frontiers in Immunology, 2024)
This investigation elucidated the differences in humoral and H1N1 HA-specific memory B-cells response in participants exhibiting distinct immune response patterns prior to and after vaccination with Fluzone, the quadrivalent split-inactivated seasonal influenza virus vaccine. Participants were categorized into persistent non-responders and persistent responders based on their hemagglutination-inhibition (HAI) antibody titers to the H1N1 component from each vaccine administered between the 2019-2020 to 2023-2024 seasons. Persistent responders had higher fold change in H1N1 HA-specific CD21 expressing B-cells, plasmablasts, and plasma cells. A significant increase in H1N1 HA-specific transitional B-cells in persistent non-responders was observed. The frequency and fold change of H1N1-specific IgM-expressing memory B-cells was higher in persistent non-responders. Dimensionality reduction analysis also demonstrated higher IgM expression for persistent non-responders than persistent responders. Furthermore, persistent non-responders had a significant fold change increase in IgA tissue-like memory, IgG exhausted tissue-like memory, and double negative (DN) activated memory cells. In contrast, persistent responders had increased frequency of IgG-activated memory B-cells, IgG resting B-cells and DN resting B-cells. Correlation analysis revealed a positive correlation between HAI titers and DN memory B-cells and a negative correlation between HAI titers and IgG-expressing memory B-cells in persistent non-responders. Conversely, persistent responders had a positive correlation between HAI titers and IgA resting memory B-cells and a negative correlation between IgG memory B-cells and DN memory B-cells. Overall, this study provided valuable insights into the differential immune memory B-cell responses following influenza virus vaccination and paves the way for future research to further unravel the complexities of vaccine-induced memory B-cells and ultimately improve vaccination strategies against influenza virus infection.